Phylogenetic and morphological analysis of the Afroedura nivaria (Reptilia: Gekkonidae) species complex in South Africa - Makhubo, Buyisile Getrude (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.